2020
DOI: 10.23950/jcmk/9256
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom toxicity in academic literature: Holistic analysis of the global publications on mushroom poisoning between 1975 and 2019

Abstract: Background and objective: Mushroom poisoning is one of the global public health problems. In our study, we aimed to analyze bibliometric and scientometric analysis of mushroom poisoning between 1975 and 2019.Methods: All data used in the present study were retrieved from Web of Science databases titled Web of Science Core Collection, Russian Science Citation Index, SciELO Citation Index and Korean Journal Database.Results: A total of 3508 documents were yielded from our preliminary WoS database search. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…As mostly previously studies [11][12][13][14][15][16][17], our study showed that the majority of articles from USA. This may due to research findings and large number of researchers in USA.…”
Section: Discussionsupporting
confidence: 85%
“…As mostly previously studies [11][12][13][14][15][16][17], our study showed that the majority of articles from USA. This may due to research findings and large number of researchers in USA.…”
Section: Discussionsupporting
confidence: 85%